An Investigation on the Subject of Women in the Thoughts of Anton Chekhov Based on the Latest Story by the Author, The Lady Bride - Zeinab Sadeghi Sahlabad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In this article, while examining Chekhov's latest story entitled The Lady Bride, the author's views on the issue of women in the last stages of her literary development are examined. To understand Chekhov in this regard, one must be aware of the historical context in which the work was created. Also, while examining the story, the symbolism of the name of the work and the name of its hero, the special fate of the hero and the reason for the open end of the story have been examined. Chekhov created the story at a time when Russia was undergoing rapid changes and it was time to open new doors to the future, but there was still no clear vision for the future, yet the author hoped for a young force and its impact on the country's destiny. And this issue is quite visible in his latest work. The present study answers the question of who is Chekhov's ideal female heroine. Chekhov's ideal female protagonist was different from other Russian writers. If at the beginning of the nineteenth century, Decembrist women who went into exile with their husbands were considered the ideal women of Russia, in the late nineteenth century, women who were able to determine their own destiny were the ideal women of society.